ANALISA PENGARUH PROMOSI, CITRA MEREK, DAN KUALITAS LAYANAN TERHADAP MINAT PENGGUNAAN APLIKASI FINTECH - Reyhan Zhafran (2020)
This quantitative research aims to determine the effect of promotion, brand image, and service quality on the interest in using fintech applications. The population in this study is the user of the fintech application. A total of 75 respondents were taken for this study, with the method used was non-probability sampling especially purposive sampling. Data collection is done by distributing questionnaires. For the analysis technique used is the PLS (Partial Least Square) analysis method using SmartPLS3.0 software. With the results of research in the form of (1) Promotion has a significant influence on interest in use with a path coefficient of 0.605. (2) Brand Image has insignificant influence on usage interest with a path coefficient value of 0.257 (3) Service Quality has an insignificant effect on usage interest with a path coefficient value of 0.015. The highest contribution is on the influence of promotion on interest in using the path coefficient of 0.605